The School principles’ Accountability in Management of Education Financing - Kemara Jati Nugroho; Matin Matin; Siti Zulaikha (STAI Hubbulwathan Duri, 2022)
This study was conducted with the aim of analyzing the school principles’ accountability in management of education financing at Gunungsari 01 Elementary School Pamijahan district, Bogor regency. The dimensions of accountability for education financing are seen from management transparency (conceptual skills), the school principles’ performance standard (technical skills), and the partnership with school committees (human skills). The approach used is a case study by collecting the observation data, interview, and document studies. The informants of this research are the school principle, treasure, teachers, operator, committees, and supervisors. The data were obtained by using qualitative analysis. The steps of this research are data reduction, data presentation, and data verification. The result of the first research is about the transparency of education financing (conceptual skills) which consist of the planning, usage, reporting, and supervision. Indicator transparency in education financing (conceptual skills) which consist of the ability of school needs, having new idea as the outline in education financing, being anticipative of the change, and be able to see the school development opportunities through education financing that have emerges but need the consistency improvement in its activities. The second point is about the school principle performance (technical skills). The indicator of technical skills regarding the school principles’ understanding of school program planning and professionalism in managing education financing with transparency and accountable which have been seen, but it needs improvement in terms of supporting document. The third point, the partnership with school committees (human skills). The human skills indicator consist of a) the ability of communication effectively in organization, b) accommodate the needs of students, parents, and school committees, c) collaboration with others, d) delegation of the taks which has been carried out well but needs to increase the intensity of the partnership period.